PERAN KELUARGA SEBAGAI MEDIA PEMBELAJARAN KECERDASAN SPIRITUAL YANG BERBASIS PANDANGAN SAYYED HOSSEIN NASR - Akbar, Zainuri (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2024)
This research is about how the family plays a role as a stimulator in building spiritual intelligence based on the Neo-Sufism views of Sayyed Hossein Nasr. That the family can be a container for a learning system for humans in cultivating character and personality. Character cultivation from within the family is significantly expected to be able to equip someone in achieving an understanding of spiritual meaning. Based on these reasons, this study attempts to provide a formulation for modern society in building spiritual intelligence based on a family approach. This study uses a qualitative analytical literature research method to reveal phenomena holistically and contextually. The results of the study show that modern society is increasingly losing its understanding of spiritual behavior, resulting in sensitivity to social conditions that are less vigilant and attentive. This study shows that in Nasr's view, the family does not only function as a place to gain worldly knowledge, but also for the good of the hereafter. Through teaching religious values, practicing joint worship, and strengthening mutually supportive emotional relationships, families can create an atmosphere conducive to the development of spiritual intelligence.